STUDENT’S PERCEPTIONS AND EXPERIENCES IN KINESTHETIC LEARNING: CHALLENGES AND BENEFITS - Joko Abadi Simamora; Iskandar Iskandar; Sukardi Weda; Muh Tahir (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study explores students' perceptions and experiences in kinesthetic learning, particularly focusing on its challenges and benefits. Conducted at the Merchant Marine Polytechnic of Makassar between November 2024 and January 2025, the research employed a qualitative approach through observations and interviews. The study aimed to understand how kinesthetic learning activities (KLAs) influence student engagement, motivation, and speaking development. Data analysis which includes data condensation, data display, and conclusion drawing. Findings indicate that students generally perceive KLAs positively, appreciating their interactive and engaging nature. Students reported higher levels of motivation and retention when movement and hands-on activities were incorporated. Active participation was evident in discussions, role-plays, and tasks requiring physical interaction, fostering a more dynamic learning environment. The use of props and physical movement significantly contributed to enhancing students' learning experiences and practical application of knowledge, particularly in maritime-related contexts. Despite these advantages, several challenges emerged. Some students experienced physical fatigue after prolonged movement-based tasks, though this did not significantly affect their focus. Limited classroom space was another obstacle, restricting students' ability to fully engage in KLAs. Additionally, the lack of sufficient tools and props hindered the effectiveness of hands-on learning. Overall, the study confirms that KLAs enhance student engagement and learning effectiveness, particularly in improving speaking skills and motivation. However, to maximize their benefits, educational institutions must address challenges related to classroom space and resource availability. Future research could further investigate the long-term impact of KLAs on skill development in vocational education